Circumventing Sanctions: The Impact of Sino-Iranian Relations On Iran Within The Middle-East Power Constellation (Case Study of Iran-Israel Proxy War in Syria) - Patricia Patricia; Kinanti Aristawidya; Marchelle Adriani (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2022)
Due to its hostile behavior in the Middle East, Iran has been sanctioned severely by the international community. Despite isolation attempts by the international community, Iran is nevertheless regarded as a powerhouse in the regional power constellation, owing to its actions in the Middle-Eastern proxy wars. Acknowledging the anomaly of Iran’s capabilities in spite of heavy sanctions, this research arguably shows how Sino-Iranian relations paves the way for Iran to circumvent sanctions. Subsequent to learning about China’s support for Iran, this research questions if the aforementioned support has an impact on Iran’s actions and status within the regional power constellation. Furthermore, this research also questions the influence of Iran and China’s relations towards the former’s ability in pursuing its aims through the Syrian proxy war against Israel in the account of international sanctions and condemnations. Guided by the concept of balancing by Stephen M. Walt and an exploitative model of proxy warfare theory, this research finds the Sino-Iranian relations as having a significant effect towards improving Tehran’s capabilities and acquisition of power in the Middle-East power constellation. Moreover, concerning the Iran-Israel proxy war, China’s actions are proven to mainly affect Iran and the Syrian civil war within the political sphere.